Behind a Veil of Ignorance?
X, 243 p. 7 illus., 4 illus. in color.
Keywords: This volume is a very interesting research project that includes the most careful work on constitutional power and limits to authority of which I am aware. In general, the contributors find that constitutional negotiations normally took place in settings where uncertainty was considerable. They also find that the more detailed the characterization of power relationships, the more liberal and durable the democracy tends to be. Roger D. Congleton This book addresses the issue of the impact of uncertainty in constitutional design. To what extent do constitution drafters and adopters make their decisions behind a veil of ignorance? More fundamentally, can we infer from constitutional texts the degree of uncertainty faced by constitution drafters and adopters? After an introduction (chapter 1), the book proceeds in two parts. The first part (chapters 2 to 4) introduces to the intellectual filiation of the project and to its theoretical and methodological foundations. The second part (chapters 5 to 13) presents nine case studies built on the same structure: historical account of the making of the Constitution, results of the content analysis of the constitutional text, and discussion of specific issues raised in the analysis. Chapter 14 concludes.